One Country, Two Calendars: Lunar January Effect in China's A‐Share Stock Market. (19th January 2023) - Liang, Xiaobo; Liu, Qianqiu; Zebedee, Allan A.
Abstract: In this paper, we examine the January effect in China's A‐share stock market from January 1995 to December 2019 using both the solar and lunar calendars. Consistent with the existing literature, we find the absence of a traditional January effect in the solar calendar; however, we observe a strong January effect in the lunar calendar. Moreover, the effect is much stronger in small firms. We demonstrate that the tax‐loss selling and window dressing hypotheses cannot explain the turn‐of‐the‐year effect in China. Instead, the turn‐of‐the‐year effect in trading volume and buy orders help to explain the strong lunar January effect. As a falsification test, we examine the B‐share market that is predominantly composed of foreign investors and find no evidence of the lunar January effect. Our results show that Chinese financial markets are more closely aligned with the traditional lunar calendar than the standard solar calendar.